Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.014
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance of Retail Industry Before and After E-Commerce Booming in Indonesia: A Study of Altman Z-Score Model

Abstract: In recent years, many modern retail outlets are reported to close down their operation due to the financial downturn. Changes in a shopping behavior pattern that consumers prefer shopping online were blamed for the closure of the store. This article aims to examine whether there is any difference in the performance of the retail industry before and after e-commerce booming in companies listed on the Indonesia Stock Exchange. This study observes the financial statement of the industry in the period 2013-2017 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…The outcome of the study, however, contradicts the views of Ika et al [13] who observed that increasing online activities such as selling online have insignificant effects of enterprises financial performance. Their focus, however, was on performance in general but not resilience as was the case in the current study.…”
Section: Moderating Role Of Enterprise Size and Ownership Type On The...contrasting
confidence: 99%
“…The outcome of the study, however, contradicts the views of Ika et al [13] who observed that increasing online activities such as selling online have insignificant effects of enterprises financial performance. Their focus, however, was on performance in general but not resilience as was the case in the current study.…”
Section: Moderating Role Of Enterprise Size and Ownership Type On The...contrasting
confidence: 99%
“…For measuring the economic sustainability, following previous studies (26,27) this study employs the Altman Z-score bankruptcy prediction model (28). Previous researches (29)(30)(31),supports the use of the Altman Z score to assess financial condition. The formula to calculate the Altman Z score is as follows:…”
Section: Variable Definition and Data Testingmentioning
confidence: 88%
“…Figure 1 depicts the production of prominent mining products in the country in 2020. Nickel leads Indonesia's mining industry with an output of 35.5 million metric tons, followed by gold and silver with 29.69 million metric tons, and bauxite with 26 million metric tons. COVID-19 officially reached Indonesia in early March 2020, at the time when President Joko Widodo announced the first confirmed infection case in the country.…”
Section: Introductionmentioning
confidence: 99%
“…This research also utilizes Altman Z-rating of financially distressed estimation model [18] to assess the healthiness of the financial condition of the sample company. Some studies have used the model to explain the impact of some economic events, such as the worldwide financial meltdown [21] and ecommerce booming [22], on the performance of a specific industry sector. Other studies have employed the model to assess financial healthiness of companies in an industry [23,24].…”
Section: Variable Measurement and Data Analysismentioning
confidence: 99%